Utilization of Black Cotton Soil Stabilized with Brick Dust-Lime for Pavement Road Construction: An Experimental and Numerical Approach - Damtew Melese; Belete Aymelo; Tewodros Weldesenbet; Alemineh Sorsa (The Baltic Journal of Road and Bridge Engineering)
Black cotton soil is highly susceptible to volume change due to moisture fluctuations. This leads to the deformation of structures built on such soil. Therefore, the aim of this study is to improve the soil-bearing capacity and deformation analysis of black cotton soil. The laboratory tests were done according to the American Association State of highway and Transport Official (AASHTO) and the American Society for Testing and Materials (ASTM). These tests were natural moisture content, grain size distribution, X-ray diffraction test, Atterberg limit test, modified compaction, California bearing ratio, and triaxial test. Soil sample was stabilized with a ratio of 0%, 4%, 8%, 12%, and 16% of brick dust and 0%, 1%, 3%, 5%, and 7% of lime, respectively. The result of the laboratory test at the optimum percentage of 12% brick dust and 5% lime shows that the liquid limit improved from 93.2% to 67.5%, plastic limit improved from 48.71%, to 58.2%. The optimum moisture content improved from 26.76 to18.5% and Maximum dry density improved from 1.42 g/cm3 to 1.58 g/cm3. The California bearing ratio improved from 1.29%, to 13.6%. The deformation analysis result shows that at optimum percentage of stabilizing agent, the deformation reduced from 2.087 mm to 0.973 mm. Therefore, brick dust-lime soil stabilization shows the promising improvement of weak subgrade soil.